1969
DOI: 10.1139/p69-335
|View full text |Cite
|
Sign up to set email alerts
|

New electronic transitions of the C2 molecule in absorption in the vacuum ultraviolet region

Abstract: Three new electronic transitions of the C2 molecule have been observed in absorption in the region 1300–1450 Å. The system of shortest wavelength is readily identified as a 1Πu–1Σg+ transition; the lower state is the ground state X1Σg+ of the molecule. The other two systems arise by absorption from the low-lying a3Πu state; the upper states are new 3Σg− and 3Δg states. Rotational and vibrational constants of the three new states have been determined. The new states are Rydberg states. Their correlation to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
1
1

Year Published

1973
1973
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 0 publications
3
25
1
1
Order By: Relevance
“…Its potential energy curve is affected by avoided crossings at about 2.8 Bohr with the curves associated with 3 1 Π u and 4 1 Π u , yielding 3 bound vibrational levels for the F state. We note that Herzberg et al (1969) observed the lower two levels, which are also the only ones associated with interstellar spectra. The depth of the potential well is about 0.5 eV.…”
supporting
confidence: 51%
See 3 more Smart Citations
“…Its potential energy curve is affected by avoided crossings at about 2.8 Bohr with the curves associated with 3 1 Π u and 4 1 Π u , yielding 3 bound vibrational levels for the F state. We note that Herzberg et al (1969) observed the lower two levels, which are also the only ones associated with interstellar spectra. The depth of the potential well is about 0.5 eV.…”
supporting
confidence: 51%
“…The only laboratory-based spectroscopic study is that of Herzberg et al (1969), whose molecular constants are used for analysis of interstellar absorption. The derivation of these constants relied on lines with J ′′ ≥ 10 for the most part.…”
Section: F − X Bandsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most prominent electronic system in the visible region is the Swan system, which involves the electronic transition d 3 Π g -a 3 Π u , with the (0,0) band near 19400 cm −1 . The a 3 Π u state was originally believed to be the ground state [26] as it was observed to be easily excited, which is because it lies only 1536 cm −1 above the actual X 1 Σ + g ground state. The Swan system has been investigated extensively.…”
Section: Introductionmentioning
confidence: 99%